PENGEMBANGAN RPP IPS SD MATERI PROKLAMATOR KEMERDEKAAN INDONESIA YANG MENGINTEGRASIKAN 4C, PPK, LITERASI, DAN HOTS - Karomah, Melisa (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to develop an Implementation Plan for Social Science Learning in Elementary Schools on the material of the Proclamation of Indonesian Independence which integrates creative thinking skills, Strengthening Character Education, Literacy, and High-Level Thinking in students. The method used in this research is a type of research and development (R&D) which is a research method used to research so as to produce new products and then to test the effectiveness of these products. The results of this study are the integration of creative, critical thinking, character strengthening, reading activities (literacy), and conducting assessments that are carried out with high-order thinking oriented questions. That way the learning implementation process can be expected to be student-centered to foster character and strong behavior towards students.